OMEGA-3 FATTY ACIDS AND AGE-RELATED DISEASES: REALITIES AND PROSPECTS - O. M. Drapkina; R. N. Shepel' (Рациональная фармакотерапия в кардиологии)
Efficacy of omega-3 fatty acids in cardiology is so high that in many countries omega-3 fatty acids are included into the treatment protocols for patients with cardiovascular diseases. This therapeutic class slows down oxidative stress and chronic inflammation processes, thereby providing a significant contribution to the complex treatment of hypertension. Besides, omega-3 fatty acids slow down the aging process and prevent the development of age-related diseases affecting the rate of telomere shortening.